Characterisation and nonlinear optical properties of CdS nano-particles. (3rd August 2009) - Majles Ara, M.H.; Dehghani, Z.; Saievar Iranizad, E.
CdS nano-particles have been synthesised using chemical precipitation. The formation and microstructure of CdS nano-particles were monitored by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-Vis spectrum and z-scan technique. Using the UV-Visible, the band gap of this nano-particle is obtained about 3.54 eV and the spectrum of this material shows a 310 nm peak. X-ray diffraction pattern (XRD) shows that the obtained CdS nanostructures are of hexagonal phase and indicates that the average crystallite size is 1.2 nm. Average particle size obtained from SEM analysis about 4.35 nm and agree with XRD result. Optical limiting property of CdS nano-particles is studied, the linear absorption coefficient was obtained about 0.044 cm−1. Furthermore the nonlinear refractive index, n2, and nonlinear absorption coefficient, β, were measured using close and open aperture z-scan respectively using a CW He-Ne laser at 632.8 nm. As nano-particles have strong absorption coefficient to obtain purely effective n2 we divided the closed aperture transmittance by the corresponding open aperture in the same incident beam intensity. The nonlinear refraction index of this nano-particle was measured in order of 10−7 (cm²/W) with positive sign and the nonlinear absorption coefficient was obtained in order of 10−3 (cm/W)) with negative sign.